The EC and the changes in Central and Eastern Europe - Rudolf Hrbek (Intereconomics, 1990)
Political developments in Central and Eastern Europe and the process of German unification present the EC with a major challenge. How has the EC reacted to these changes so far? What contribution can the eC make to overcoming the division of Europe?
Keywords: 330; East-West Relations